Unbalanced fermentation of glycerol in Escherichia coli via heterologous production of an electron transport chain and electrode interaction in microbial electrochemical cells. (June 2015) - Sturm-Richter, Katrin; Golitsch, Frederik; Sturm, Gunnar; Kipf, Elena; Dittrich, André; Beblawy, Sebastian; Kerzenmacher, Sven; Gescher, Johannes
Highlights: Anaerobic glycerol fermentation in Escherichia coli can be accelerated to an anode. Functional screen for heterologous cytochromes with respiratory activity in E. coli. Development of an inducible methylene blue-assisted anode respiration system. New electron transport chain contains the cytochromes CymA, MtrA and STC. Abstract: Microbial electrochemical cells are an emerging technology for achieving unbalanced fermentations. However, organisms that can serve as potential biocatalysts for this application are limited by their narrow substrate spectrum. This study describes the reprogramming of Escherichia coli for the efficient use of anodes as electron acceptors. Electron transfer into the periplasm was accelerated by 183% via heterologous expression of the c -type cytochromes CymA, MtrA and STC from Shewanella oneidensis. STC was identified as a target for heterologous expression via a two-stage screening approach. First, mass spectroscopic analysis revealed natively expressed cytochromes in S. oneidensis . Thereafter, the corresponding genes were cloned and expressed in E. coli to quantify periplasmic electron transfer activity using methylene blue. This redox dye was further used to expand electron transfer to carbon electrode surfaces. The results demonstrate that E. coli can be reprogrammed from glycerol fermentation to respiration upon production of the new electron transport chain.